2014
DOI: 10.1161/circresaha.114.302625
|View full text |Cite
|
Sign up to set email alerts
|

Lung Natural Killer Cells Play a Major Counter-Regulatory Role in Pulmonary Vascular Hyperpermeability After Myocardial Infarction

Abstract: Rationale: Natural killer (NK) cells are lymphocytes of the innate immune system that play specialized and nichespecific roles in distinct organs. Objective:We investigated the possible function of NK cells in the pathogenesis of congestive heart failure after myocardial infarction. Methods and Results: Depletion of NK cells from mice had little effect on cytokine expression (tumor necrosisfactor-α, interleukin [IL]-6, and IL-1β), neutrophil and macrophage infiltration into infarcted myocardium, or left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Vascular hyperpermeability is a common pathogenic process which is often found during the development of several malignant diseases such as diabetic retinopathy [53], solid tumors [35], myocardial infarction [54], wounds [15], and chronic inflammation [28]. The determining structure of vascular permeability [34] is endothelial integrity, which is tightly controlled by many types of signals such as physiological factors (VEGF, TNF or INFγ), oxidative stress and pro-inflammatory cytokines [1,20].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular hyperpermeability is a common pathogenic process which is often found during the development of several malignant diseases such as diabetic retinopathy [53], solid tumors [35], myocardial infarction [54], wounds [15], and chronic inflammation [28]. The determining structure of vascular permeability [34] is endothelial integrity, which is tightly controlled by many types of signals such as physiological factors (VEGF, TNF or INFγ), oxidative stress and pro-inflammatory cytokines [1,20].…”
Section: Introductionmentioning
confidence: 99%
“…Although a clear role for inflammatory IFN-g-producing NKs is established in systemic inflammation (11,12), defining a role for IL-10-producing NKs requires more experimental evidence. However, it is possible that NK-derived IL-10 plays a regulatory role in preventing further damage to the organism, as was shown in the case of myocardial infarction (39).…”
Section: Discussionmentioning
confidence: 98%
“…Neutrophils are recruited to the alveolar space and lung interstitium, thereby producing large quantities of chemokines, such as chemokines KC (CXCL‐1) and MIP‐2 (CXCL‐2) (Lerner, Lei, Sundar, & Rahman, ; Rancan et al, ), and reactive oxygen species (ROS) (Spassov et al, ), and neutrophils play critical roles in the development of ALI. Alveolar macrophages also play important roles in the release many pro‐inflammatory cytokines, such as IL‐1β, TNF‐α, and IL‐6 (Parpaleix et al, ; Yan et al, ). In this study, the functional analysis demonstrated that both Ad‐PGRN and Ad‐PGRN‐shRNA caused significant changes in PGRN expression in vivo and that these changes were sustained for a long time.…”
Section: Discussionmentioning
confidence: 99%